ANALISIS PENGGUNAAN ENERGI LISTRIK PADA BANGUAN GEDUNG LABORATORIUM BENGKEL ELEKTRONIKA POLITEKNIK NEGERI PONTIANAK - Medi Yuwono Tharam; Wendhi Yuniarto; Hasan (Jurnal ELIT, 2026)
Abstract Electric energy plays a vital role in everyday life and is utilized for a number of things, including industry, transportation, and lighting. Government Regulation No. 70 of 2009 and other energy conservation measures are among the many laws that control energy use to preserve efficiency. One of the biggest users of power is the building industry, which uses energy for a number of utilities. The 27 educational facilities at Politeknik Negeri Pontianak include labs that run computers, practical equipment, and other auxiliary equipment. This study backs up the government's energy efficiency program for the educational sector, which should be implemented without sacrificing comfort. The study's findings indicate that the Laboratory/Workshop building's electrical energy performance satisfies all applicable PLN, Minister of Energy and Mineral Resources Regulation No. 4 of 2009, and ANSI C84 criteria. Keywords: Building, Efficiency, and Electrical Energy Performance